Człowiek i bycie. O ograniczaniu podmiotowości w późnej twórczości Czesława Miłosza - Gleń, Adrian (Przestrzenie Teorii, 2007)
The text tackles the question of the phenomenon of being, one of the crucial issues in Mitosz's late poetry. The author analyzes Mitosz's various strategies of constructing and deconstructing the subject, and interprets them as conscious acts which make man's perception of Being possible. At the article's core stands the poet's inter-semiotic dialogue with Martin Heidegger's philosophy of language as set around the question of the articulation of existence in the poetic word.